Análise do uso da andiroba (Carapa guianensis Aubl) na perspectiva do conhecimento tradicional e científico, da proteção intelectual e da atividade anti-Leishmania do óleo e frações. - OLIVEIRA, Iara dos Santos da Silva (2018)
In the Amazon region, andiroba oil is one of the products most used by the population due to its medicinal properties. The oil can be used for a number of purposes, such as bruises, inflammations, verminoses, for healing and recovery of the skin, throat affections, coughs, ear infections. There is a wide variety of application of the products in commercial scale or traditional use. The objective of this work wasto analyze the developed and patented research on this species, to describe the chemical composition of the oil and fractions, to evaluate its anti-Leishmania activity and to analyze the use of andiroba in the traditional knowledge perspective in the region of Baixo Munin, of Maranhão. The Lens.org website and public databases of the Brazilian Patent and Trademark Office (INPI), United States Patent and Trademark Office (USPTO), the European Patent Office (EPO), the LATPAT - Espacenet and the World Intellectual Property Organization (WIPO) were used for the research of scientific and technological publications. The anti-Leishmania activity was evaluated against the promastigotes and intracellular amastigotes of Leishmania amazonensis. For the study of the extractive communities in the Munin region, the methodology of case studies with application of forms and interviews with members involved in the andiroba production chain. Products related to patent search terms were mainly aimed at pharmaceuticals, cosmetics, repellents, production processes and various utilities. Despite the large number of publications related to taxonomic and ecological studies, studies on the chemical properties and biological activity of the species were highlighted. The scientific studies found are mainly related to the antiparasitic, anti-inflammatory, healing, antimicrobial, anti proliferative and antioxidant activities of andiroba. Three fractions of oil showed activity against promastigotes (IC50 of 10.53, 25.30 and 56.90 μg/mL) and intracellular amastigotes (IC50 of 27.31, 78.42 and 352.20 μg/mL) of L. amazonensis, as well as cytotoxicity against peritoneal macrophages (CC50 of 78.55, 139.0 and 607.7 μg/mL). The anti-Leishmania activity of the fractions of C. guianensis can be attributed to the limonoids of the gedunin and andirobine group detected in the chemical analysis. It was verified that extractive activity of andiroba was carried out in forest regions by extractivists, with the participation of other members of the productive chain, the middlemen, soap manufacturers and consumers. It was found that the members of the production chain are organized mainly for the processing of andiroba oil for local soap factories.